Exploring the Impact of Pilgrimage Tourism on the Community - Julungwangi, Anindita Maya (International Journal of Psychosocial Rehabilitation, 2020)
this study focused on the case of pilgrimage to sacred graveyard among Muslim people in the Javanese society in Indonesia. Pilgrimage to sacred graveyard become a promising tourism sector to be develop. There are thousands of graves that are visited every day in one year round. The research conducted in Gunungpring Sacred Graveyard, Central Java, Indonesia. By examining the recent pilgrimage pehonomenon, the finding will discuss about the impact brought by pilgrimage tourism to the community.